Efficacy of 10% povidone iodine versus 70% alcohol in umbilical cord care of newborn infants - Rasyidah Rasyidah; Yulizar Yulizar; Lily Emsyah; Guslihan D Tjipta; Dachrul Aldy (Paediatrica Indonesiana, 2005)
Objective To compare the effectiveness of 10% povidone iodineto that of 70% alcohol in umbilical cord care of newborn infants.Methods This open label clinical trial was conducted in PirngadiHospital, Medan from July to September 2003. Newborn infantswho fulfilled inclusion criteria were randomly allocated to umbili-cal cord care using 10% povidone iodine or 70% alcohol. Themain outcome measures were omphalitis prevalence, microor-ganism colonization, and time to umbilical cord separation. Cultureof the umbilical cord swab was taken in the first 48-72 hoursafter birth. The umbilical cord was observed daily during hospital-ization and every other day after discharge until cord separation.Statistical analysis was done using chi-square test and indepen-dent t-test.Results There were 54 infants in the povidone iodine group and52 infants in the alcohol group. Omphalitis was absent in bothgroups. Fourteen percent of subjects in the povidone iodine groupshowed no microorganism growth, compared to 7% in the alco-hol group. Staphylococcus aureus colonization was found in10% of subjects in the povidone iodine group and 23% of sub-jects in the alcohol group. The prevalence of Escherichia colicolonization was 41% and 47% in the povidone iodine and alco-hol groups, respectively. There was no statistically significantdifference between both groups in bacterial colonization (P=0.135).Mean time to umbilical cord separation was 6.44 days in thepovidone iodine group and 6.13 days in the alcohol group(P=0.431).Conclusion These results suggest that 10% povidone iodineand 70% alcohol are equally effective in umbilical cord care ofnewborn infants